Design and validation of a grinding wheel optical scanner system to repeatedly measure and characterize wheel surface topography. (November 2016) - McDonald, Andrew; Bauer, Robert; Warkentin, Andrew
Highlights: Development of a grinding-wheel scanner with a vision-based wheel-homing system. Development of a new friction-wheel slip-correction system. Development of a new analysis method to establish the true grinding wheel surface. Scanner results validated with Scanning Electron Microscope (SEM) imaging. Results include cutting edge number, width and area as a function of radial depth. Abstract: This paper describes the design and validation of an upgraded grinding wheel scanner system that controls the position of a Nanovea CHR-150 Axial Chromatism sensor along the x - and y -directions of the wheel surface to measure and characterize wheel surface topography. The scanner features a novel homing system that enables the wheel to be removed from the scanner, used on a grinding machine and then re-mounted and re-homed so that the same location on the wheel surface can be repeatedly measured and monitored. The average standard deviation for homing was 27.6 μm and 19.3 μm in the x - and y -directions, respectively, which is more than adequate for typical area scans of 25 mm 2 . After homing, the scanner was able to repeatedly measure features that were similar in size to an abrasive grain (∼200 μm diameter) with an average error of 9.3 μm and 5.9 μm in the x - and y -directions, respectively. The resulting topography measurements were compared with Scanning Electron Microscope images to demonstrate the accuracy of the scanner. A custom particle filter was developed to process the resulting data and a novel analysis technique involving the rate of change of measured area was proposed as a method for establishing the reference wheel surface from which desired wheel topography results can be reported such as the number of cutting edges, cutting edge width and cutting edge area as a function of radial depth.